Back to basics. Issue 4 (13th November 2017) - Fox, Robert
Abstract : Purpose: This paper aims to explore several methods for developing an effective content model for library websites. Design/methodology/approach: This paper is conceptual. Originality/value: Websites can take a couple of approaches to design. One is "top down" that focuses on the User Interface (UI) and graphic design. Another is "bottom up" that focuses on the organization of content. This paper encourages website designers to take a more "bottom up" approach to web design.